EVALUATION AND INHIBITORY MECHANISM ANALYSIS OF NATURAL COMPOUNDS AGAINTS DIHYDROOROTATE DEHYDROGENASE AS ANTI-CANCER AGENTS - Aji Wibowo; Danang Waluyo; Bimo Ario Tejo; Tinta Komariyah; Ariza Yandwiputra Besari; Erwahyuni Endang Prabandari (BRIN - Badan Riset dan Inovasi Nasional, 2023)
Cancer remains one of the deadliest diseases worldwide, and currently cancer treatment is facing several problems related to adverse effects and drug resistance. To address these problems, new prospective anticancer medications are required. Natural compounds, which have been extensively used in the drug research, including for the treatment of cancer, are emerging as viable candidates. This study aimed to evaluate 33 in-house natural compounds against dihydroorotate dehydrogenase (DHODH) enzyme, a viable target to develop anticancer agent, and to analyze the hit inhibitory mechanism against protein target. In the activity assay, atovaquone was the sole substance to have activity against DHODH, with an inhibition rate of 47.44% at 10 µM. However, discrepancies were shown in the molecular docking result, where atovaquone were identified as hits. Molecular dynamic analysis revealed that atovaquone initially bound to the active site before being forced to the outside due to cleavage of hydrogen bond between the ligand and responsible residue. This study clearly demonstrated the importance of molecular dynamic analysis to study inhibitory mechanism of compound against target protein that may be useful for further development.